The Effect of The Intelligence Games Preschool Program on The Math Skills of 60-72 Month-Old Children - Yüzbaşıoğlu, Yasemin (Southeast Asia Early Childhood Journal, 2023)
This study was conducted to examine the effect of the Intelligence Games Preschool Program on the math skills of 60-72 month-old children. In the research, a model with pre-test post-test control group, which is one of the quasi-experimental models, was used. A total of 30 children, 15 of them from the experimental group and 15 of the control group, participated in the study. General Information Form and TEMA 3 Mathematics Ability Test were used as data collection tools in the study. In addition to the Preschool Education Program of the Ministry of National Education, the children constituting the experimental group in the study were included in the Intelligence Games Preschool Program prepared by the General Directorate of Lifelong Learning for 10 weeks, every day and 2 hours a week for a total of 100 hours. The control group was not included in this program and continued with the Ministry of National Education Preschool Education Program. Mann Whitney U test was used for comparison of independent measurements and Wilcoxon Signed Ranks test was used for comparison of related measurements in the analysis. Based on the research findings, it was concluded that intelligence games contribute to children's basic mathematical skills such as counting, comparison, addition and extraction process, matching, rhythmic counting, matching objects and numbers, visual perception and concept of part and whole.